Rovibrational transitions and nuclear spin conversion of methane in parahydrogen crystals - Miki, Masaaki; Momose, Takamasa (Физика низких температур, 2000)
Solid parahydrogen is an excellent matrix for matrix-isolation spectroscopy because of its high spectral resolution. Here we describe the rovibrational structure and nuclear spin conversion of CH₄ embedded in parahydrogen crystals studied by infrared absorption spectroscopy. The vibration–rotation absorptions of CH₄ exhibit time-dependent intensity changes at 4.8 K. These changes are interpreted to be a result of the I=1→I=2 nuclear spin conversion that accompanies the J=1→J=0 rotational relaxation. The half-lifetime of the upper J=1 rotational state is unchanged by the addition of up to 2% orthohydrogen molecules but decreases with more than 10% orthohydrogen molecules. The increase of the decay rate at higher orthohydrogen concentration indicates that the magnetic field gradient across CH₄ due to the orthohydrogen molecules mixes the nuclear spin states, which accelerates the conversion.